The Marshall plan for novel writing A 16-step program guaranteed to take you from idea to completed manuscript - Marshall, Evan frey50 (Cincinnati, Ohio Writer's Digest Books, 2001)
Imagine writing with the skill of a published author, the knowledge of a seasoned editor and the savvy of a New York literary agent...you'd have all the know-how it takes to transform your story idea into a novel worthy of praise and publication. In this unique guide, agent, editor and novelist Evan Marshall does give you everything it takes to write your novel. Drawing on his extensive experience, Marshall has perfected a simple and methodical approach to novel writing. His clear-cut, 16-step "Marshall Plan" breaks down the complex novel-writing process into a series of parts you put together one piece at a time. You'll have your whole story planned and plotted before you actually begin writing, so there's no chance of working yourself into a corner or making critical mistakes in pacing and plot. In short, The Marshall Plan for Novel Writing works. Use it, and watch your story masterfully develop into a completed manuscript ready to get the full attention of readers, agents and editors alike.
Introduction -- How the plan works -- Planning for success -- Finding the perfect novel for you -- Shaping your story idea -- Creating your lead -- Defining your other characters -- Your complete guide to plotting -- Getting off to the right start -- Interweaving story lines -- Surprising the reader -- Ending on all the right notes -- How to write fiction like a pro -- Putting it all together -- Mastering the modes I: Action, summary, dialogue -- Mastering the modes II: feelings/thoughts and background -- Completing a draft -- Polishing your manuscript -- How to be your own editor -- Applying the finishing touches -- Marketing your novel -- Producing a knockout proposal -- Approaching agents and editors - Glossary -- Appendix A: Sample synopsis -- Index.
Includes index.
Keywords: Fiction -- Authorship; Creative writing